Optical Character Recognition Mobile App for Address Matching in Integrated Social Welfare Data Verification Process - Panjaitan, RE. Miracle; Rahayudi, Bayu; Ratnawati, Dian Eka (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
The Ministry of Social Affairs of the Republic of Indonesia has Integrated Social Welfare Data called Data Terpadu Kesejahteraan Sosial (DTKS) and uses it as a basis for the distribution of Social Fund Assistance, or Bantuan Sosial (BANSOS). The fact that occurred in the field was that there were many BANSOS recipients who were not impoverished and did not qualify to be the target of this program. One of the reasons is that there are weaknesses in the system that have the potential for data manipulation during the verification and validation processes. Therefore, a system improvement is needed to minimize the possibility of the data being manipulated. This study proposes a digital verification system using Optical Character Recognition (OCR) and reverse geocoding to make sure that the registrant provides their own citizen ID card and their own house address that meet the qualifications. These technologies in the developed mobile app perform address matching between address extracted from citizen ID card and address obtained from reverse geocoding. The results of this application trial achieved a success rate of 95.7%.